Project-Based Learning (PjBL) in Mathematics and Science Classrooms: Perspectives from Three Universities in Sumatra - Hidayati, Hidayati; Al-Ikhlas; Minarni; Ansyar, Raynadra; Rusdi, Muhammad (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
Project-based learning (PjBL) is a learning innovation in which an independent learning curriculum exists. This PjBL activity is expected to be well implemented by lecturers in higher education. This study aimed to determine the implementation of PjBL in Higher Education in South Sumatra, as well as the obstacles and solutions provided. Questionnaires and interview sheets were used for data collection in this study. The research subjects were final-year students and lecturers at universities in Southern Sumatra (Palembang, Jambi, and Kerinci). The results showed that the implementation of project-based learning in three stages, namely planning, implementation, and evaluation, was categorized as very good. In this research, several obstacles were found in the implementation of PjBL activities, such as problems related to time, facilities, and infrastructure, and activating students to complete tasks both in groups and independently, so that solutions from these obstacles are offered to overcome this. The solutions that can be given include preparation of lesson plans, provision of facilities and infrastructure, providing additional time to complete the project, and integrating PjBL activities with other methods so that they could be implemented optimally.